Bilateral Metachronous Typical and Atypical Carcinoid Tumors of the Lung - Alberto Busetto; Giovanni Maria Comacchio; Vincenzo Verzeletti; Fares Shamshoum; Francesco Fortarezza; Federica Pezzuto; Andrea Dell'Amore; Fiorella Calabrese; Federico Rea (Thoracic Cancer)
ABSTRACT Bronchial carcinoids are uncommon neuroendocrine tumors. According to their pathological differentiation, they are divided into typical and atypical forms, with diverse biological behavior and aggressiveness. Bronchial carcinoids may be associated with familial neuroendocrine syndromes, such as MEN‐1. They can also present initially as diffuse hyperplastic proliferation of neuroendocrine foci throughout the pulmonary parenchyma (DIPNECH). Metachronous and bilateral forms are sporadic in the literature. We describe a case of a 68‐year‐old man with metachronous bilateral typical‐atypical carcinoid neoplasms. The patient was treated with a two‐stage mini‐invasive pulmonary surgery in a time frame of 5 years. This case may be unique because it features two rare and distinct pathological entities in the same patient, not associated with any known genetic mutation. Carcinoid tumors require multidisciplinary care and a collaborative approach due to their pleomorphic behavior, ensuring comprehensive management and maximizing therapeutic efficacy.